(untitled) (SCIENCE TIME JOURNAL, 2026)
The idea of freedom stands as one of the most vital and enduring values of humanity, holding a central position in the philosophical, cultural, and linguistic evolution of societies. Deep reflection reveals that the theoretical foundations of freedom are far richer and more multifaceted than a singular or universal conception might suggest. Across ages and myriad civilizations, languages have shaped and colored understandings of freedom, while each culture has interpreted this concept within the framework of its distinct value system, history, and social dynamics. Exploring the theoretical basis of the idea of freedom across different linguistic and cultural contexts, it becomes clear that no definition stands apart from time, place, and human experience.